Decomposition of Regional Inequality in the Usage of Mosquito Nets in Nigeria - Olabisi, Adewara, Sunday; Deborah, Irelewuyi, Moyinoluwa; Hosu, Yiseyon, S.; Mbukanma, Ifeanyi (Journal of Cultural Analysis and Social Change, 2025)
The usage of mosquito nets is one of the interventions of the government to curb malaria, yet consistent use of insecticide-treated mosquito nets is not universally applied. Despite widespread free distribution efforts, less than half of those with nets use them regularly. The study, therefore, decomposed the causes of regional inequality in the usage of mosquito nets in Nigeria. The data used for this study were from the 2021 Nigeria Malaria Indicator Surveys (NMIS). The study employed Anderson’s behavioral theory of health services utilization and used the Blinder-Oaxaca Group Differences to decompose the determinants of regional disparity in mosquito net utilization. The findings indicated that there existed regional inequality in the usage of mosquito nets in Nigeria. The result further showed that the educational gap, perception, north-south dichotomy, sex of the household head, and disparity in wealth quintile in the rural-urban areas contributed positively and significantly to the inequality in the usage of mosquito nets in the rural-urban areas in Nigeria. The findings also showed that the household age divide and perceptual differences between the Northeast and other regions impacted the North-East inequality. Also, household head age divide, and social-media usage differences between the Northwest and other regions contributed to north-west inequality, perception differences between other regions, and the southeastern regions contributed to south-east inequality in mosquito net utilization. Furthermore, household head age divide, sex of household head differences, and social-media usage differences reduced the south-south inequality, perception gap, rural-urban differences, and wealth disparity between the south and western regions, which contribute to increased south-west inequality in mosquito net utilization, and urbanization contributed to north-central inequality. This study, therefore, recommended that the government should implement region-specific education and communication strategies that would address socio-economic, gender, and perceptual disparities.